2022
DOI: 10.4049/jimmunol.2200280
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Role of mTORC1 Signaling in B Cell Immunity in Teleost Fish

Abstract: Mammalian studies have demonstrated that B cell immune responses are regulated by mechanistic target of rapamycin complex 1 (mTORC1) signaling. Teleost fish represent the oldest living bony vertebrates that contain bona fide B cells. So far, whether the regulatory mechanism of mTORC1 signaling in B cells occurred in teleost fish is still unknown. In this study, we developed a fish model by using rapamycin (RAPA) treatment to inhibit mTORC1 signaling and demonstrated the role of mTORC1 signaling in teleost B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, it should be noted that previous studies have reported conflicting findings. For example, a previous study reported that short-term exposure to RAPA may inhibit mTORC1 in mouse macrophages [ 47 , 62 ] and trout B cells [ 37 ], leading to a reduction in phagocytosis. These discrepancies are likely due to differences in phagocytosis mechanisms among different phagocytes, suggesting that mTORC1 signaling may regulate phagocytosis through distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that previous studies have reported conflicting findings. For example, a previous study reported that short-term exposure to RAPA may inhibit mTORC1 in mouse macrophages [ 47 , 62 ] and trout B cells [ 37 ], leading to a reduction in phagocytosis. These discrepancies are likely due to differences in phagocytosis mechanisms among different phagocytes, suggesting that mTORC1 signaling may regulate phagocytosis through distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To gain granulocytes, we first isolated leukocytes from the head kidney as described previously [ 37 ] with modifications. Briefly, largemouth bass head kidneys were treated with DMEM (Gibco™, Gaithersburg, MD, USA) supplemented with 5% FBS (Gibco™, Amarillo, TX, USA) and mechanically disaggregated on a 100 μm nylon cell strainer (SPL life sciences, Gyeonggi-do, Republic of Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferation of IgZ + B cell and IgM + B cell was analyzed by flow cytometry, as previously described. 52 WT and TLR2-KO zebrafish were anesthetized with MS-222 and injected with 5 μg of 5-ethynyl-29deoxyuridine (EdU, Invitrogen). After 24 h, leukocytes from the gill and spleen were sampled, as described above.…”
Section: Effects Of Tlr2 On Vaccine-induced Apc Activationmentioning
confidence: 99%
“…64 The conserved role of MAPK, NF-κB, and mTORC1 signaling pathways in adaptive immunity was also confirmed in teleost fish. 52,65 B cells and Igs represent the most important components of the adaptive immune system in vertebrates. 39 Specific B cells represent the most important components of the adaptive immune system of vertebrates.…”
Section: Lsg-tdh Induces Apc Activation By Interacting With Tlr2mentioning
confidence: 99%